Solution of the stochastic point kinetics equations using the implicit Euler-Maruyama method - Suescún-Díaz, Daniel; Oviedo-Torres, Yohan M.; Girón-Cruz, Luis E. (Annals of nuclear energy, 2018)
•The approximations obtained are better than those derived from other methods.•The method used significantly decreases the standard deviation.•This method is easy to implement and has a lower computational cost. In this work, the implicit Euler-Maruyama method is used to solve the stochastic point kinetics equations for different forms of reactivity: constant, linear and sinusoidal. A covariance matrix is proposed considering the one-speed diffusion theory of a nuclear reactor subject to the initial condition applying to the pulsed neutron methods. The results obtained with this method are more efficient in the calculation of neutron densities and delayed neutron precursors. It was possible to reduce the standard deviation with a very good precision for the expected values.